(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Database Security is a growing concern evidenced by an increase in the number of reported incidencesof loss of or unauthorized exposure to sensitive data. As the amount of data collected, retained and shared electronically expands, so does the need to understand database security. Security models, developed for databases differ in many aspects because they focus on different features of the database security problem or because they make different assumptions about what constitutes a secure database. This paper explains the need for a database trigger and it role in enforcing the various database security challenges.